Dekolonisasi Tata Kelola Iklim: Kritik Postkolonial terhadap Pembiayaan Iklim Internasional - Erlangga, Raditya; Muhammad Arshy Sallatu (JPP (Jurnal Politik Profetik), 2026)
This article critically examines global climate finance governance through a postcolonial lens, focusing on how schemes such as the Green Climate Fund (GCF) reproduce colonial structures in knowledge–power relations. Methodologically, it employs a qualitative approach with Norman Fairclough’s Critical Dis-course Analysis of UNFCCC documents, statements by Global South states in COP negotiations, and technocratic narratives institutionalized by Global North actors. The findings show that climate finance regimes sustain epistemic inequities through indicators, proposal formats, and development rhetoric rooted in European modernity, thereby positioning Global South countries and Indigenous peoples as passive recipients rather than knowledge producers or equal partners in climate policy design. Drawing on decolonial thought, the study foregrounds epistemic disobedience as a strategy to contest Western epistemic hegemony and to advance recognition of plural ways of knowing. Case studies from Indonesia, Tuvalu, Vanuatu, Bolivia, and several African countries illustrate forms of resistance articulated through diplomacy, local spiritualities, and international legal initiatives that frame the climate crisis as part of a colonial legacy. The article contributes to critical International Relations by highlighting a research gap on coloniality in environmental regimes and argues that decolonizing climate governance requires not only redistributing funds but also redistributing legitimacy, representation, and political–epistemic capacity to shape just climate solutions.